Mappable Nearly Orthogonal Arrays Using Projective Geometry - POONAM SINGH, MUKTA D. MAZUMDER, SANTOSH BABU, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The finite projective geometry is used to construct many series of symmetric orthogonal arrays of strength two and more. In this paper, we propose a method of construction of Nearly orthogonal arrays mappable into fully symmetric orthogonal arrays of strength two finite projective geometry.